The Limits of Inventing Tradition: The Dravidian Movement in South India - Weiss, Rick (Journal for the academic study of religion, 2007)
Eric Hobsbawm and Terence Rangers’ influential volume, The Invention of Tradition, remains a milestone in scholarly approaches to the study of tradition. However, in emphasizing conscious manipulations of tradition, and in employing a notion of invention that lacks nuance, the authors of that volume do not sufficiently acknowledge the degree to which invented traditions draw from prior traditions. I explore here the limits of conscious constructions of tradition, arguing that traditions that serve as powerful touchstones for identity cannot be invented ex nihilo. I look at an instance of elite formulation of tradition, the Dravidian Movement in Tamil Nadu, South India, in the first half of the twentieth century, which articulated a new formulation of Tamil tradition based largely on European models and ideals. The leaders of this movement envisioned an ancient Tamil community that was egalitarian, scientific, and non-Hindu, and they employed this vision in their development of policies for education, religious institutions, and industrialization. Their failure to mobilize popular support for their cause was repeatedly demonstrated in their electoral defeats at the hands of the Congress Party, which promoted a reformist tradition based on Hindu symbols and ritual practices. I argue that the Dravidian Movement failed to win political support because they discarded nearly all the components of prior Tamil tradition, and the novel tradition they authored in turn was unrecognizable to ordinary Tamils.